Nanostructured hafnium-doped strontium oxide film for homeotropic/homogeneous convertible liquid crystal alignment depending on the curing temperature - Dong Hyun Kim; Dong Wook Lee; Jin Young Oh; Jonghoon Won; Hae-Chang Jeong; Dae-Shik Seo (International Journal of Smart and Nano Materials, 2022)
ABSTRACTA hafnium strontium oxide (HfSrO) liquid crystal (LC) alignment film was efficiently created through brush coating, and its ability to change the LC alignment direction was confirmed. A brush was applied to HfSrO sol coated on an indium-tin oxide substrate, after which the coating was solidified at various curing temperatures. It was confirmed that a directional micro/nanostructure was formed above 280°C due to the shear stresses caused by the movement of the brush hairs. Surface chemical changes were analyzed by using X-ray photoelectron spectroscopy and contact angle measurements. As the curing temperature increased, the prevalence of oxygen bonds increased and the contact angle decreased, thereby increasing the surface energy. The anisotropic boundary of the microgrooves and the van der Waals forces due to an increase in surface energy changed the alignment direction of LC molecules from vertical to horizontal, as verified through polarized optical microscopy and pretilt angle measurements. Thus, the efficiency of the brush-coating method, which dramatically simplifies the LC alignment film process, was confirmed. The homeotropic/homogeneous LC alignment property of the HfSrO film produced through brush coating depending on the curing temperature provides an innovative approach for LC alignment.